Keputusan Pembelian Berdasar Persepsi Kualitas Produk dan Ekuitas Merek : (Purchasing Decisions Based on Perceptions of Product Quality and Brand Equity) - Eka Giovana Asti; Widodo Widodo; Eka Avianti Ayuningtyas (LPPM Universitas Pelita Bangsa, 2021)
One way to increase sales is by implementing a marketing mix, but in this study we will focus on two strategies to increase sales, namely the Product Strategy and Brand Equity. Products are the starting point for success and failure in marketing as a whole, therefore every entrepreneur must know and understand various important aspects of the product to be marketed and entrepreneurs must be able to understand what benefits buyers of their products can expect. Meanwhile, brand equity is a factor that can influence consumers to repurchase the same brand. Consumers think that it is more economical and efficient than consumers have to go back to find out about other brands. Both of these activities are thought to support increased sales. But to what extent these two strategies can increase sales will be analyzed in this study by taking 70 samples. The type of method used is quantitative method. The results of this study indicate that there is a partial influence between Product Strategy and Brand Equity on the Sales Level at the Present Drink Outlets in Depok City. And so is the correlation coefficient between Product Strategy and Brand Equity together on the Sales Level of Present Drinks Outlet in Depok City, is positive with a very strong level of relationship that is equal to 0.903 and after testing the hypothesis with the F test the correlation has a significant relationship. Then the results of the regression coefficient test show a straight and positive relationship seen from the contribution Product Strategy and Brand Equity on the Sales Level of Present Drinks Outlet in Depok City, namely with the equation: Ŷ = 25.686 + 0.442X1 + 0.423X2 Keywords: Brand Equity, Product Strategy, Sales Level